Collective efforts to fight fall armyworm (FAW) led to FAW-tolerant varieties in only 2 years and dedicated IPM extension efforts reaching 187,000 farmers - CGIAR Research Program on Maize (2021)
Fall armyworm has become an endemic pest across Africa and Asia. International efforts enabled monitoring and surveillance and dissemination of sustainable and affordable Integrated Pest Management and breeding-based solutions. Control strategies that combined intercropping, crop rotation and adjusting planting/harvesting dates have proved promising. Within 2 years, CIMMYT made available FAW-tolerant hybrids for sub-Saharan Africa (SSA). In 2021, National Agricultural Research System (NARS) partners started national performance trials. In Asia, smallholder extension efforts in Bangladesh reached 187,000 farmers during 2020-2021.